Acknowledgment to Reviewers of Antibiotics in 2020 - Antibiotics Editorial Office (MDPI AG, 2021)
Peer review is the driving force of journal development, and reviewers are gatekeepers who ensure that Antibiotics maintains its standards for the high quality of its published papers [...]